Adenosine kinase and adenosine receptors A1R and A2AR in temporal lobe epilepsy and hippocampal sclerosis and association with risk factors for SUDEP. (3rd April 2020) - Patodia, Smriti; Paradiso, Beatrice; Garcia, Maria; Ellis, Matthew; Diehl, Beate; Thom, Maria; Devinsky, Orrin
Abstract: Objective: The "adenosine hypothesis of SUDEP" (sudden unexpected death in epilepsy) predicts that a seizure‐induced adenosine surge combined with impaired metabolic clearance can foster lethal apnea or cardiac arrest. Changes in adenosine receptor density and adenosine kinase (ADK) occur in surgical epilepsy patients. Our aim was to correlate the distribution of ADK and adenosine A2A and A1 receptors (A2A R and A1 R) in surgical tissue from patients with temporal lobe epilepsy and hippocampal sclerosis (TLE/HS) with SUDEP risk factors. Methods: In 75 cases, patients were stratified into high‐risk (n = 16), medium‐risk (n = 11) and low‐risk (n = 48) categories according to the frequency of generalized seizures before surgery. Using whole‐slide scanning Definiens image analysis we quantified the labeling index (LI) for ADK, A2A R, and A1 R in seven regions of interest: temporal cortex, temporal lobe white matter, CA1, CA4, dentate gyrus, subiculum, and amygdala and relative to glial and neuronal densities with glial fibrillary acidic protein (GFAP) and neuronal nuclear antigen (NeuN). Results: A1 R showed predominant neuronal, A2A R astroglial, and ADK nuclear labeling in all regions but with significant variation. Compared with the low‐risk group, the high‐risk group had significantly lower A2A R LI in the temporal cortex. In HS cases with severe neuronal cell loss and gliosis predominantly in the CA1 and CA4 regions, significantly higher A1 R was present in the amygdala in high‐risk than in low‐risk cases. There was no significant difference in neuronal loss or gliosis between the risk groups or differences for ADK labeling. Significance: Reduced cortical A2A R suggests glial dysfunction and impaired adenosine modulation in response to seizures in patients at higher risk for SUDEP. Increased neuronal A1 R in the high‐risk group could contribute to periictal amygdala dysfunction in SUDEP.